Governança em rede: estudo da estrutura relacional no projeto A Cor da Cultura - Otavio Rezende (2014)
The overall objective of this thesis is to identify and analyze how the relational structure of the interorganizational network 'the Color of the Culture' influences its governance structure. The study refers to the third edition of the project, held between 2013 and 2014. To this aim, the theoretical framework focuses on the relationship of individuals in the context of the network governance, on the contribution of the Structural Sociology to understand how status, power and domination operate; and how Social Network Analysis can be used to apprehend informal relations in such context. Therefore, this study sought to contribute to the understanding of networks coordination processes involving the relationship between public, private and civil society organizations, including informal relations. Due to the nature of the problem, we adopt a descriptive method, using qualitative and quantitative data analysis. Three forms of data collection were used. Primary data refer to semi-structured interviews conducted to 19 managers and educational group coordinators in order to understand the formal and informal governance and application of sociometric questionnaires to 101 involving members of the core executive management group and implementers of the sub network. As a source of secondary data, we had access to the project of sponsorship application, which was used to constitute and negotiate with sponsoring institutions, meeting reports, managerial reports, surveys and contracts. In order to identify central positions of the analyzed network, a whole network and blockmodelling analysis were methods used to identify measures of the network structure. The results demonstrate concentration of resources in a core group of actors who bring prestige, prominence and influence from other fields. Although they hold leadership positions in the meso level of the formal structure of the network, their prominent position generates informal power over the whole network. Future studies suggested may: a) consider actors perception from adjacent fields related to the network; b) take further accuracy on identifying positions of leadership, technical advice, cooperation and friendship; c) evaluate the network performance, comparing individuals performance to the effect of lateral control mechanisms; d) identify the individual type of rational decision making, in order to unveil a possible relationship of cause and effect in the context of interaction of informal relationships occurring in the context of network governance.